Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s12913-019-3878-7
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated service delivery: a qualitative study of people living with HIV and accessing care in a tertiary facility in Ghana

Abstract: BackgroundIn 2014, the Joint United Nations Program on HIV/AIDS (UNAIDS) set out a treatment target with the objective to help end the AIDS epidemic by 2030. This was supported by the UNAIDS ’90-90-90’ target that by 2020, 90% of all people living with HIV (PLHIV) will know their HIV status; 90% of all those diagnosed with HIV will be on sustained antiretroviral therapy; and 90% of all people receiving antiretroviral therapy will have viral suppression. The concept of offering differentiated care services usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
65
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 25 publications
8
65
5
Order By: Relevance
“…Contrary to what has been reported in the literature about the benefits realized by patients such as savings in transport costs and time spent at facilities via DSD when compared to more intensive undifferentiated care models [14], [18], [30], [32] our findings suggest that the picture is more complex and patients have other considerations in the models of HIV care they prefer. For instance, some patients in our study sample, preferred frequent clinic visits with a few expressing a willingness to spend money and time despite awareness of the benefits of DSD in reducing the burden of treatment.…”
Section: Patientscontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to what has been reported in the literature about the benefits realized by patients such as savings in transport costs and time spent at facilities via DSD when compared to more intensive undifferentiated care models [14], [18], [30], [32] our findings suggest that the picture is more complex and patients have other considerations in the models of HIV care they prefer. For instance, some patients in our study sample, preferred frequent clinic visits with a few expressing a willingness to spend money and time despite awareness of the benefits of DSD in reducing the burden of treatment.…”
Section: Patientscontrasting
confidence: 99%
“…Although DSD has been rolled-out nationally in several countries since WHO's landmark 2016 guidelines were released, there is a dearth of evidence on patient perspectives on HIV care under DSD in 'real world' settings or at the frontline level of service delivery [15]- [17]. A notable exception is a study conducted in Ghana [18]. However, that study only reported patient experiences of DSD from one tertiary hospital in Cape Coast Ghana.…”
mentioning
confidence: 99%
“…This aligns with other studies where home counseling and testing was considered as one of the most effective strategies to reach more people [17] and attend to family preference for home counseling and testing due to issues of privacy and con dentiality [4,18,19]. In contrast a study among people living with HIV in this same setting had revealed a fear of accidental disclosure associated with communitybased service provision [20]. This is an indication that there is no conclusive evidence of home -based testing being the preferred option over facility-based service.…”
Section: Discussionsupporting
confidence: 82%
“…A study evaluating the impact of spaced clinic appointments for clients with HIV (6 months versus 1 month) found that 30% were removed from 6-month dispensing due to having unstable medical conditions such as decreased CD4 counts, ART regimen changes, pregnancy, nonadherence, and drug toxicity. 22 If 6-month dispensing is taken to scale, clients should be counseled about coming to the ART clinic without delay for any new health issues. Providers should receive appropriate training about when to shift clients to shorter intervals due to poor adherence/virologic failure, side effects, after regimen changes, or during pregnancy.…”
Section: Discussionmentioning
confidence: 99%